Impact of Anterior Clinoid Process Pneumatization on Adjacent Anatomical Structures - Elsawaf, Manal E. (Academia Anatomica International, 2017)
The Anterior clinoid process is closely related to many important anatomical structures including vessels, nerves, and paranasal sinuses. In the majority of cases, this process is osseous, but its pneumatization has been recorded as an anatomic variant. Coronal CT scans of the head region that were done for thirty-seven patients at Tanta University hospitals were collected to be used in teaching radiological anatomy for medical students. During their routine investigation, a case of a female aged 21 years showed bilateral pneumatization of the anterior clinoid processes associated with some variants of the adjacent anatomical structures. These findings were discussed on anatomical basis with referral to their possible clinical implications. If a surgical removal of the anterior clinoid process is recommended, a comprehensive knowledge of its anatomy, pneumatization, and associated regional anatomic variants is crucial for neurosurgeons to avoid risky complications.